A feasibility study on elbow erosion monitoring using active sensing approach and fractional Fourier transform. (March 2021) - Li, Ning; Wang, Furui; Song, Gangbing
Elbow erosion monitoring is of great significance to the safety of pipeline systems and maintenance personnel. This paper proposes a new elbow erosion monitoring method, which combines the PZT (lead zirconate titanate) enabled active sensing with the fractional Fourier transform (FrRT), and takes the fractional-order energy peak of the stress wave signal as the damage index. Three 90°-elbows and three 90°-elbow assemblies were used in the experimental studies. Under different erosion degrees, the mass reduction of the three separate elbows was measured by high-precision electronic scale and the residual thickness of the three elbow assemblies was detected by ultrasonic thickness gauge. Two pieces of PZT patches were respectively used to excite and receive the signals in the active sensing. FrFT was used to distinguish the linear sweep signal components of stress wave signals from the energy of other interference or noise signals, and the fractional-order energy peak was used as the damage index. The results show that there is a one-to-one relationship between mass of erosion loss and damage index. Compared with the traditional time domain signal energy method, the new method has the advantage of eliminating the saturation phenomenon. The proposed method and damage index proposed in this paper will be a promising tool for real-time monitoring of elbow erosion.